Regional state innovation in peripheral regions: enabling Lapland’s green policies - Morales Arcila, Diana (2021)
How do sparsely populated regions innovate in green policies? What enables or limits such innovation? The green policy literature often focuses on core regions, while territorial innovation models have long ignored regional state innovation. In this article we examine the drivers of public sector innovation in green policies in peripheral regions, often considered unequipped. The data come from the case study of Finnish Lapland's Smart Specialisation Strategy in relation to promoting a forest-based bioeconomy. In a context where climate change has become a major global challenge, and sustainable development an additional responsibility for local and regional governments, this article contributes to understanding the rationales for innovation in green policies from a regional perspective. Drawing from institutional economic geography, we argue that top-down approaches (Smart Specialisation) combined with scale and place-specificity (personal connections, environmental fragility, political will and natural resources endowments) play an important role in driving the governments of sparsely populated regions to innovate when translating and implementing green policies.